Synthesis of organotin derivatives of optically active eleven-membered macrodiolides - Scoccia, Jimena (2016)
The synthesis and the results obtained in the hydrostannation of eight new TADDOL diacrylates and methacrylates are reported. The addition of triorganotin hydrides, R3SnH, 12-14 (R = nBu, neophyl, Ph, respectively) to diesters 6-11 containing different combinations of substituents at the C-2 carbon of the dioxolane ring, led to macrocyclization products in all cases. The cyclohydrostannation of diacrylate 10 proceeded with complete diastereoselectivity. The cyclohydrostannation of diesters 33 and 34 with hydrides 12 and 14 in all cases only afforded one stannylated macrocycle.